microRNA-210 overexpression inhibits tumor growth and potentially reverses gemcitabine resistance in pancreatic cancer - Amponsah, Prince Saforo; Fan, Pei; Bauer, Nathalie; Zhao, Zhefu; Gladkich, Jury; Fellenberg, Jörg; Herr, Ingrid (Cancer letters, 2017)
Resistance to first-line chemotherapies like gemcitabine contributes to high disease lethality in pancreatic cancer. By microarray and qRT-PCR, we observed significant downregulation of microRNA-210 in gemcitabine-resistant cells. The overexpression of microRNA-210 was toxic to gemcitabine-resistant cells and enhanced gemcitabine sensitivity. MicroRNA-210 overexpression induced caspase-3-mediated apoptosis, and inhibited colony formation. Computationally, ABCC5, a highly expressed gene in our array data, was identified as a potential target of microRNA-210 and the overexpression of ABCC5 in gemcitabine-resistant cells was confirmed by qRT-PCR. MicroRNA-210 overexpression reduced ABCC5 mRNA levels and inhibited a luciferase reporter expressing the ABCC5 3' UTR. The expression pattern of microRNA-210 and ABCC5 was mirrored in all of 5 pancreatic cancer cell lines used. Likewise, microRNA-210 transfection nearly totally inhibited tumor xenograft growth, proliferation and metastasis without obvious side effects in vivo. Also, an absence or low expression of microRNA-210 correlated to high ABCC5 expression in the majority of malignant patient tissues from a total of 101 patient tissues examined. Our observations provide at first glance, an important function for microRNA-210 in regulation of gemcitabine responsiveness by it's target gene ABCC5.